2005
DOI: 10.1021/ac050495g
|View full text |Cite
|
Sign up to set email alerts
|

Poly(dimethylsiloxane)-Based Microchip for Two-Dimensional Solid-Phase Extraction-Capillary Electrophoresis with an Integrated Electrospray Emitter Tip

Abstract: A microchip in poly(dimethylsiloxane) (PDMS) for in-line solid-phase extraction-capillary electrophoresis-electrospray ionization-time-of-flight mass spectrometry (SPE-CE-ESI-TOF-MS) has been developed and evaluated. The chip was fabricated in a novel one-step procedure where mixed PDMS was cast over steel wires in a mold. The removed wires defined 50-microm cylindrical channels. Fused-silica capillaries were inserted into the structure in a tight fit connection. The inner walls of the inserted fused-silica ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 32 publications
0
48
0
Order By: Relevance
“…The problems of hydrophobic surface of the PDMS were overcome for example by in-channel oxidation [8]. The coating of the walls by a positively charged polymer, PolyE-323, shows good durability in long-term tests [9,10]. Lee et al [11] reported about organic-based spin-on glass and water-soluble acrylic resinbased methods.…”
Section: Chip-based Ce-msmentioning
confidence: 99%
See 1 more Smart Citation
“…The problems of hydrophobic surface of the PDMS were overcome for example by in-channel oxidation [8]. The coating of the walls by a positively charged polymer, PolyE-323, shows good durability in long-term tests [9,10]. Lee et al [11] reported about organic-based spin-on glass and water-soluble acrylic resinbased methods.…”
Section: Chip-based Ce-msmentioning
confidence: 99%
“…Dahlin et al [10] presented an approach for 2-D SPE-CE on a chip with MS detection applying a two-level cross design on the chip. One channel provided the sample over SPE extraction, while the second capillary was applied for the separation.…”
Section: Chip-based Ce-msmentioning
confidence: 99%
“…For example, polystyrene beads 32 or C 18 -coated silica beads 33 have been incorporated into channels as solid-phase extraction (SPE) media to remove salts and other unwanted solution constituents. Alternatively, the extraction of subproteomes has been demonstrated in microflow systems via immobilized metal affinity chromatography (IMAC) beads 34 or lectin immobilized on polymer monoliths 35 for the enrichment of phosphopeptides or glycoproteins, respectively.…”
Section: Extraction Of Proteins In Channel Microfluidicsmentioning
confidence: 99%
“…For such a purpose, a variety of interfaces have been designed, including such types as valve-loop, 7,8 T-split, 9,10 valve-loop-vial or T-piece, [11][12][13][14] two-leveled two cross, 15,16 flow-gating, 11,[17][18][19][20][21] and interfaces with integrated SPE. 22,23 With the first three types of interfaces, success of the coupling has been achieved to some extent, but some limitations have been recognized. Because of the large void volume resulting from the loop and the eluate flow path between the two capillaries, serious dilution and dispersion of the elution plug have occurred, thus leading to a loss of SPE efficiency, especially when a small elution volume is used.…”
Section: Introductionmentioning
confidence: 99%